Androgen in postmenopausal women - Matsui, Sumika; Yamamoto, Satoshi; Yasui, Toshiyuki; Tani, Anna; Kunimi, Kotaro; Irahara, Minoru (The Journal of Medical Investigation, 2012)
Menopausal symptoms, bone loss, changes in lipid profiles and reduction of insulin sensitivity due to an abrupt decrease in circulating estrogen level are well known in women during the menopausal transition. On the other hand, the effect of androgen on women’s health has not been fully elucidated. Circulating levels of testosterone and dehydroepiandrosterone sulfate (DHEA-S) gradually decrease with age in postmenopausal women, although transient increases have been observed during the menopausal transition. High testosterone level has been suggested to be associated with increased risk of cardiovascular disease, increased triglyceride, insulin resistance and increase in the risk of developing breast cancer in postmenopausal women. Circulating DHEA-S level does not affect the risk of cardiovascular disease, mortality or lipid profiles in women. Female androgen insufficiency, which is characterized by the presence of reduced androgen level in circulation, leads to an impairment in sexual drive, reduced libido, depressed mood, and signs and symptoms of limited androgen exposure such as decreased muscle mass, reduced bone density and decreased sense of well-being. An appropriate level of androgen may play important roles in metabolic, psychological and sexual functions in women. In addition, the roles of testosterone and DHEA-S in women’s health may be different. J. Med. Invest. 59: 12-27, February, 2012